A Research on the Development Strategy of Quanjude, a Time-Honored Brand in China (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
China’s time-honored brands have a rich cultural heritage, carrying the history and culture of China, and they have been recognized and supported by the majority of consumers, forming strong reputations and influence. In the era of rapid development of the Internet and the impact of the new epidemic situation on the global economy, China’s time-honored brands not only usher in rare development opportunities but also face severe difficulties. This paper takes Quanjude, a well-known Chinese time-honored brand that has existed for more than 100 years, as the research object. Quanjude is loved by heads of state, government officials, people from all walks of life, and tourists at home and abroad, and it is referred to as “the first food in China.” This study used PEST, the five forces model, SWOT, and other strategic analysis tools to analyze the corporate culture and development strategy of Quanjude in detail. The results revealed it is not difficult to find that the advantages of Quanjude outweigh the disadvantages. With the expansion of the same industry, the brand characteristics of Quanjude gradually fade, and the homogenization trend begins to appear; consumers can more easily find substitutes in the industry, which will occupy a part of the market share. Quanjude’s brand, with its high popularity, and the Chinese government’s strong support for the development of time-honored enterprises can overcome their disadvantages and give full play to their advantages.